Breakage and dislocation of the Hickman catheter in pediatric patient - Stevanović Vesna; Krunić Igor; Prijić Sergej; Vujić Dragana (Srpski Arhiv za Celokupno Lekarstvo)
Introduction. The Hickman catheter is a tunneled, open-type catheter often implanted in children for long-term intravenous treatment. Their application can cause numerous complications. Catheter breakage and dislocation of fragments to the intravascular system is a rare but life-threatening condition. When a complication occurs, depending on the patient’s clinical condition, the first step is transcutaneous endovascular removal of the catheter’s fragment. If this is not possible, surgical thoracotomy is necessary. The objective of this article was to present a case of breakage and dislocation of Hickman catheter in a pediatric patient, as well as the diagnostic and therapeutic approach to complications. Case outline. We report a 14-month-old child who had a Hickman catheter because he was undergoing treatment for acute juvenile myelomonocytic leukemia. Due to a malfunction of the catheter, the existing catheter had to be removed. During the surgical procedure, a breakage and dislocation of the catheter fragment occurred. A chest X-ray and an echocardiography confirmed the position of the catheter fragment in the right atrium. A transcutaneous endovascular procedure was successfully performed to remove the fragment of the catheter. Conclusion. Numerous complications can occur during the insertion, management, and removal of longterm catheters. It is necessary to periodically control the catheter’s position by chest X-ray and ultrasound of the heart and neck. If a particular complication is detected, an individual approach to treatment with the lowest risk to the patient should be chosen. Dislocated fragments of the Hickman catheter can be safely removed by endovascular transcatheter procedures.